Experimental Infection with Parent and L-Phase Variants of Neisseria meningitidis - Bohnhoff, Marjorie (1968)
Thirty-six strains of Neisseria meningitidis, including groups A, B, and C, produced L forms in vitro in the presence of an osmotic stabilizer and high concentrations of horse serum using penicillin as the transforming agent. Transformation to L growth occurred most readily among strains recently isolated from patients, and an unusually high rate of transformation was observed in 7 of the 36 strains. Revertant L strains developed diplococcal colonies on blood-agar and L colonies on sucrose-serum-penicillin-agar—always in a ratio of approximately 10 to 100 diplococcal colonies to 1 L colony. Using mucin as a host depressant, comparison was made between parent and revertant L strains of their initial pathogenicity and development of virulence by serial mouse passage. In general, revertant L strains showed the same pathogenic characteristics as the parent. Heart blood cultures from mice dying of infection with revertant L strains retained their ability to grow as L forms on penicillin media. Three stable L strains were completely avirulent for mice, although persistence of L forms could be demonstrated in peritoneal exudate for 6 days after inoculation.